Agricultural knowledge management: Case of dairy production improvement Bure Woreda, West Gojjam Zone, Amhara Region - Assefa, H. (Addis Ababa University, 2010)
The government of Ethiopia gives great attention to agriculture and rural development for the country’s economy development. Dairy development is one of the components of agricultural development. To improve dairy production in certain locality, dairy producers should able to access and use appropriate knowledge for the particular problem at the right time. This research was conducted to assess agricultural knowledge management system and its challenges and opportunities of knowledge management processes in Bure district. To address these objectives, both primary and secondary data were used. These were collected from primary (i.e. dairy producers and experts of different GOs and NGOs using semi-structured questionnaire and checklist) and secondary sources (i.e. literature reviews). To select representative respondents, multi stage sampling techniques were used. SPSS software (version 15) was used to analysis the data which is collected by questionnaire. As survey result, the major objective of the majority respondents engaged in dairy farming is for milk consumption and obtaining ox for draught power. Keeping the health condition of animals, feed green pasture to their milking cows, animal selection and using crossbreed cow are the major mechanisms, which are used by dairy producers, to improve the milk production in the district. They obtain these knowledge/mechanisms from WARDO, their own experience neighbors and family through different means. These are observing the farmer’s farm, listening to radio, experience sharing sessions and on-farm demonstrations.. Majority of the dairy producers use the new knowledge by doing partial modification. They also transferred their knowledge to their neighbors, friends, relative and children. Dairy production in the district is not market oriented, rather it use for household consumption and obtaining ox for draught power. Therefore, to change this production system into market oriented, concerned bodies should provide adequate dairy technologies and trainings to dairy producers. Besides, promoting and strengthening the existing good practices in knowledge managements processes.